CRITICAL APPROACH TO LITHUANIAN FOREIGN POLICY: WHAT HAD CHANGED SINCE AUGUSTINAS VOLDEMARAS’S TIMES? - Laurinavičius, Česlovas; Lopata, Raimundas; Sirutavičius, Vladas (Politologija, 2015)
In the article, Lithuanian foreign policy is analysed as paying specific attention to the link between the national identity and foreign policy. According to the authors, this link could be the key in analysing the question, if in truth Lithuanian foreign policy has reached a particular point, which could be named as international isolation or at least a tendency towards it, and if yes, – then why? Critically, authors are discussing what has been done during the past five years in the field of Lithuanian foreign policy. It is suggested that Lithuania has abandoned the attitudes of the bridgehead and outpost, and the actions based on the conflict, nonappellant integrity and vain preaching. At the same time it is essential not to forget one of the most important conditions, thanks to which, for instance, membership in the Alliance became real, this is the principle of sound coexistence with neighbours which was mentioned on numerous occasions. Undoubtedly this rule is relevant in regard to EU membership. Whilst using the advantages of Euro-Atlantic structures, the faulty “bandwagoning” bait should be put away and try to move to the normal balancing in the boundaries of Lithuanian collective commitments. Briefly, Lithuania has to start being more self confident. First of all, in the Lithuanian foreign policy it would mean the implementation of a rational syncretism for solving the problem of the national identification and the state geopolitical code compatibility. Corrections in domestic politics are needful as well. It should move to the democratic “legalisation” of the existing Lithuanian political trends. This should help to defeat the especially vicious practice, when politicians are afraid of the charges of post soviet collaboration, particularly distinguished by the “actions against soviet heritage” campaigns, actually brought Lithuanian policy to the interest of foreign countries. That is exactly why it is worth coming back one more time to the so called lustration process, naming it more precisely the – soviet inheritance denial process. It is obvious, that the current spread of this process, its extent and forms are not ser-ving the Lithuanian political moral climate and national security, because during the current process two different subjects are confounded: the discloser of the foreign countries agents and internal political action. Of course the line between them could be vague sometimes, but it will exist if the struggle among various political orientations will work out democratically, and the threat from the foreign agency will be differentiated. One way the agency is expressing its threat when the state is leading the confrontational foreign policy, and the other – when keeping the constructive international relationship. Herewith, it is noticed that it would be a big mistake to go to the extremes, eventually even trying to reconsider the feasibility of EU and NATO membership. Euro-Atlantic institutions remain the major guarantee of stability in Europe, including Lithuania. Once again it is necessary to underline, that the change of foreign policy course in any case is risky. First of all because changing the foreign policy direction could inevitably change the power distribution structure, in which Lithuania exists. It could stimulate the particular retreat of the USA, the progressive dissociation of the European Union, and Russia would fill the emerged vacuum. It is likely, that Russia would interpret the changes in Lithuanian foreign policy as a sign of weakness and would strengthen the imperial pressure. Also, the assumption, that the USAwould express it’s discontentment in particular means: starting with financial and finishing with eventual secret destabilising actions, should not be eliminated. However, presumptive difficulties shouldn’t intimidate, raise pessimistic moods and lead to passivity. The refusal of the destructive orientation, it means zero summation game as the specific practice in the state foreign policy, and shifting to the positive, “win-win” paradigm would mean the change of the orientation in the cooperation partners selection – from various power action exponent to zero summation players. It is also necessary to keep in mind that previously discussed Lithuanian foreign policy faults considerably settled because of the inadequate reality signals sent by Lithuania about itself and about the real or assumed dangers.